Analysis of the factors influencing child labour in tobacco farming: The case of Urambo district - Benedicto, Daimon (Mzumbe University, 2024)
A dissertation submitted in partial fulfillment of the requirements for the award of the Degree of Masters of Science in Economics (MSc. Economics) of Mzumbe University